ACTIVE METHODOLOGIES IN BASIC EDUCATION: THE ECOLOGICAL TRAIL AS A STRATEGY FOR MEDIATING LEARNING IN ENVIRONMENTAL EDUCATION - Rodrigues, Zelinda Duarte; Brabo, Nina Rodrigues; Tavares, Patrícia Alves; Moreira, Auricilene Gomes; Rodrigues, Rosária Duarte; Fernandes, Nancy Santos; de Andrade, Ló Martins; Ribeiro, Karla Tereza Silva (Seven Editora, 2026)
Active methodologies have stood out in Basic Education for promoting student protagonism and the meaningful construction of knowledge. This article, derived from a master’s dissertation, analyzes the application of an ecological trail game as a tool for mediating learning in fifth-grade classes of Elementary Education in three public schools in the municipality of São Sebastião da Boa Vista (PA), involving 205 students. The research, with a qualitative approach and a descriptive and exploratory nature, used participant observation, recorded through a systematic monitoring checklist of students’ interactions during the activity. Structured based on the municipality’s map, the game problematizes local socio-environmental challenges, with an emphasis on water conservation for human consumption, articulating skills outlined in the Brazilian National Common Curricular Base (BNCC). The results show high student engagement, expansion of critical reflection, and strengthening of environmental awareness, as well as interdisciplinary integration among different curricular components. It is concluded that the ecological trail constitutes an effective teaching resource in mediating the teaching-learning process, contributing to the development of critical individuals and to the strengthening of contextualized practices in Science Education.